2010
DOI: 10.1152/ajpregu.00449.2010
|View full text |Cite
|
Sign up to set email alerts
|

Neurodegeneration in an animal model of Parkinson's disease is exacerbated by a high-fat diet

Abstract: (PD), the clinical literature remains equivocal. We, therefore, sought to address the relationship between insulin resistance and nigrostriatal dopamine (DA) in a preclinical animal model. High-fat feeding in rodents is an established model of insulin resistance, characterized by increased adiposity, systemic oxidative stress, and hyperglycemia. We subjected rats to a normal chow or high-fat diet for 5 wk before infusing 6-hydroxydopamine (6-OHDA) into the medial forebrain bundle. Our goal was to determine whe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

6
97
0

Year Published

2011
2011
2022
2022

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 131 publications
(103 citation statements)
references
References 57 publications
6
97
0
Order By: Relevance
“…In this study, rotational behavior was successfully evoked by amphetamine for all experimental rats, indicating unilateral nigrostriatal DA depletion. Similar to our previous studies (Morris et al, 2010), we did not measure significant differences in net rotations between HF and Chow rats. This result was may have been due a lack of diet effect on dopamine receptor stimulation, or that the HF feeding did not influence DA levels greatly enough to lead to behavioral differences.…”
Section: Discussionsupporting
confidence: 72%
See 3 more Smart Citations
“…In this study, rotational behavior was successfully evoked by amphetamine for all experimental rats, indicating unilateral nigrostriatal DA depletion. Similar to our previous studies (Morris et al, 2010), we did not measure significant differences in net rotations between HF and Chow rats. This result was may have been due a lack of diet effect on dopamine receptor stimulation, or that the HF feeding did not influence DA levels greatly enough to lead to behavioral differences.…”
Section: Discussionsupporting
confidence: 72%
“…Our previous studies have used Fischer 344 rats fed a high-fat diet to model diet-induced obesity with insulin resistance (Morris et al, 2010), and reported that HF feeding can impair glucose tolerance (Gupte et al, 2009). In the current study, we found a reduction in body weight when adult male Fischer 344 rats fed a high-fat diet for 13 weeks were switched to low-fat diet.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Choi et al, 2005). Likewise, rats under high-fat diet for 5 weeks before 6-OHDA infusion into the medial forebrain bundle exhibit greater dopamine depletion in the substantia nigra and striatum, and increased oxidative stress than control rats (Morris et al, 2010). Confirming the protective effect of caloric restriction, susceptibility to a neurotoxic insult to dopaminergic neurons is exacerbated in obese mice (Sriram et al, 2002).…”
Section: Is There a Gdnf Diet?mentioning
confidence: 94%